Corrugated Bruch′s membrane in high myopia - Jonas, Jost B. (Acta ophthalmologica, 2018)
Purpose To assess the appearance of Bruch′s membrane (BM) in axially elongated eyes. Methods The light-microscopical investigation included histological anterior-posterior sections of human eyes. Using a light microscope, we assessed whether BM in the posterior segment was straight or locally corrugated. Corrugation of BM was defined as an elevation of BM with a height >20 μm over a basis of 50 μm without collateral proliferations of retinal pigment epithelium or choroidal swelling. Results The investigation included 85 eyes (age: 62.0 ± 14.1 years; axial length: 26.7 ± 3.5 mm). In multivariate analysis, the presence of a corrugated BM, detected in eight eyes (9.4%), was strongly associated with the presence of macular BM defects [p = 0.001; odds ratio (OR): 418; 95% confidence interval (CI): 1 215 000], but not with axial length (p = 0.54). Bruch′s membrane (BM) corrugation was detected in seven (54%) of 13 eyes with macular BM defects. The single eye with BM corrugation and without macular BM defect showed the corrugated BM located in the parapapillary region at the peripheral end of a large parapapillary gamma zone. Conclusion Bruch′s membrane (BM) corrugation can be present in the vicinity of macular BM defects in highly myopic eyes, perhaps due to differences in the tension within BM in various regions at the margin of the BM defect. Bruch′s membrane (BM) corrugation may also develop at the papillary end of BM in eyes with a large parapapillary gamma zone, potentially due to a disinsertion of BM at the end of the peripapillary choroidal border tissue of Jacoby. The observation of BM corrugation may help elucidating the aetiology of axial myopia.
Gesehen am 17.06.2020
First published: 13 December 2017